(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Objective: To conduct a comprehensive assessment of anthropometric indicators in children aged 7-12 years living in industrial areas of Tashkent region and determine the impact of industrial factors on physical development. Methods: The study included 1,149 children (main group - 1,019 children, control group - 130 children). Anthropometric measurements were performed using standardized methods. Statistical analysis was conducted using descriptive and analytical statistics methods. Results: The negative impact of industrial areas was clearly manifested in boys - over 5 years, height growth was 4.45 cm less and body weight was 2.68 kg less. A paradoxical situation was identified in girls - girls living in industrial areas often showed better development. Sexual dimorphism intensified from age 11 and reached maximum level at age 12. Conclusion: The impact of industrial areas on children’s anthropometry depends on gender and age. Boys are more sensitive to industrial factors. Special monitoring and preventive measures are necessary.